Chiral Metal–Organic Frameworks - Gong, Wei; Chen, Zhijie; Dong, Jinqiao; Liu, Yan; Cui, Yong (Chemical reviews, 2022)
In the past two decades, metal–organic frameworks (MOFs) or porous coordination polymers (PCPs) assembled from metal ions or clusters and organic linkers via metal–ligand coordination bonds have captivated significant scientific interest on account of their high crystallinity, exceptional porosity, and tunable pore size, high modularity, and diverse functionality. The opportunity to achieve functional porous materials by design with promising properties, unattainable for solid-state materials in general, distinguishes MOFs from other classes of materials, in particular, traditional porous materials such as activated carbon, silica, and zeolites, thereby leading to complementary properties. Scientists have conducted intense research in the production of chiral MOF (CMOF) materials for specific applications including but not limited to chiral recognition, separation, and catalysis since the discovery of the first functional CMOF (i.e., d- or l-POST-1). At present, CMOFs have become interdisciplinary between chirality chemistry, coordination chemistry, and material chemistry, which involve in many subjects including chemistry, physics, optics, medicine, pharmacology, biology, crystal engineering, environmental science, etc. In this review, we will systematically summarize the recent progress of CMOFs regarding design strategies, synthetic approaches, and cutting-edge applications. In particular, we will highlight the successful implementation of CMOFs in asymmetric catalysis, enantioselective separation, enantioselective recognition, and sensing. We envision that this review will provide readers a good understanding of CMOF chemistry and, more importantly, facilitate research endeavors for the rational design of multifunctional CMOFs and their industrial implementation.